Ideology and Migration after the American Civil War. (7th September 2018) - Eli, Shari; Salisbury, Laura; Shertzer, Allison
Abstract : The American Civil War fractured communities in border states where families who would eventually support the Union or the Confederacy lived together prior to the conflict. We study the subsequent migration choices of Civil War veterans and their families using a unique longitudinal dataset covering enlistees from the border state of Kentucky. Nearly half of surviving Kentucky veterans moved to a new county between 1860 and 1880. We find strong evidence of sorting along ideological dimensions for veterans from both sides of the conflict. However, we find limited evidence of a positive economic return to these relocation decisions.